Psychosocial characteristics of AIDS patients with unsuppressed viral load after six months of antiretroviral therapy - Okoli, Emmanuel Ikechukwu (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.